From Personal Values to Economic Support: A Mediation Model of Attitude Toward a Low‑Carbon Tourism Economy - I Gusti Ayu Agung Pradnya Dewi; Budi Shantika; Caren Angellina Mimaki (International Journal of Management Science and Information Technology, 2026)
This study aims to examine the impact of individual values and perceived economic benefits on tourists’ intention to support Low-Carbon Tourism Economy (LCTE) by combining the Value-Belief-Norm Theory (VBN) and Theory of Planned Behavior (TPB). This research used a quantitative method by distributing survey data to 159 respondents of Generation Z who had traveled in the past year. The data were evaluated by testing the measurement model and the structural model using Structural Equation Modeling (SEM) using SmartPLS. The results reveal that biospheric and altruistic values have a significant impact on tourists’ perspective towards a low-carbon tourism sector, meanwhile egoistic values have no significant impact. Furthermore, perceived economic benefits had a direct positive and significant impact towards attitudes to support LCTE. Attitude toward LCTE was also found to strongly influence the behavioral intention and mediate correlations between biospheric and altruistic values and intention to support LCTE. However, attitude failed to mediate the relationship between egoistic ideals and intention to support. The results show that the support for the transition to low-carbon tourism is mostly driven by moral ideals and collective concern, rather than personal self-interest. Therefore, governments and tourist industry stakeholders should establish communication strategies to emphasise the ecological, social and economic benefits of transitioning towards low-carbon tourism in order to attract public support, especially among Generation Z.